2017
DOI: 10.1108/apjml-08-2016-0144
|View full text |Cite
|
Sign up to set email alerts
|

Exploring customer engagement valences in the social services

Abstract: Purpose Minimal attention is given to the negative valences of customer engagement and how they manifest in ways that detract from service value. The purpose of this paper is to uncover the meaning and conceptual dimensions of disengagement and negative engagement in conjunction with positive engagement. It explores how three valences of engagement manifest towards dual objects: the service community and the focal service organisation. This exploration is based within a new and novel social service context. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
50
0
6

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 44 publications
(58 citation statements)
references
References 89 publications
2
50
0
6
Order By: Relevance
“…Additionally, apart from a recent study that identified cognitive (subjectivity) and emotional (irritation and community intimacy) triggers of community engagement (Heinonen, 2017), the majority of existing studies on the negative valence of engagement have identified only emotional triggers, such as hatred, anger and stress, towards a service provider, brand or firm (e.g. Bowden et al, 2017;Juric, Smith and Wilks, 2016;Naumann et al, 2017).…”
Section: Influencing Behaviormentioning
confidence: 99%
“…Additionally, apart from a recent study that identified cognitive (subjectivity) and emotional (irritation and community intimacy) triggers of community engagement (Heinonen, 2017), the majority of existing studies on the negative valence of engagement have identified only emotional triggers, such as hatred, anger and stress, towards a service provider, brand or firm (e.g. Bowden et al, 2017;Juric, Smith and Wilks, 2016;Naumann et al, 2017).…”
Section: Influencing Behaviormentioning
confidence: 99%
“…Major areas of interest analysis resulted in several revelations. On the one hand, we observed that research on consumer dissatisfaction is currently more focused on discovering how to manage dissatisfied customer engagement by recovery strategies, for example, by showing how different interactions within the service ecosystem can influence engagement (Azer & Alexander, 2020; Naumann, Lay‐Hwa Bowden, & Gabbott, 2017). Furthermore, the most innovative research is trying to define which factors influence hotel customer dissatisfaction (Li, Liu, Tan, & Hu, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Negatively valenced engagement in relation to brands, can be shown through consumers’ “unfavourable brand-related thoughts, feelings, and behaviours during focal brand interactions” (Hollebeek and Chen 2014, p. 63). In the context of services, negative CE can entail feelings of “anger, hatred and stress, which manifest through more constructive coping behaviours such as individual and group complaint behaviour” (Naumann et al 2017, p. 902). More importantly, negative CE can manifest in ways that affect the wider service community beyond the focal firm, by customers who may seek to recruit others in their cause (Naumann et al 2017).…”
Section: What Is Customer Engagement?mentioning
confidence: 99%
“…In the context of services, negative CE can entail feelings of “anger, hatred and stress, which manifest through more constructive coping behaviours such as individual and group complaint behaviour” (Naumann et al 2017, p. 902). More importantly, negative CE can manifest in ways that affect the wider service community beyond the focal firm, by customers who may seek to recruit others in their cause (Naumann et al 2017).…”
Section: What Is Customer Engagement?mentioning
confidence: 99%
See 1 more Smart Citation